Hubungan Dukungan Keluarga Terhadap Kepatuhan Diet Pasien Diabetes Mellitus Tipe 2 Di Wilayah Kerja Puskesmas Gamping 1 - Kiki Kartika; Isti Suryani; Tjarono Sari (JURNAL NUTRISIA, 2017)
Background : Diabetes mellitus is a chronic metabolic disorder that can not be cured but can be controlled, characterized by hyperglycemia due to deficiency of insulin or the inadequate use of insulin. RISKESDAS in 2013 the prevalence of diabetes is highest in Yogyakarta, namely by 2.6%, the results of the study in Indonesia showed that (75%) of patients was not obeying the diet recommendation. The factor affecting obedience is a social family. Objective : This study aims to determine the relationship of family support for dietary compliance of patients with diabetes mellitus type 2 in Puskesmas Gamping 1. Method : This research using cross sectional method. This research was conducted in Puskesmas Gamping 1 in December 2016. The subject of this study is patients with diabetes melitus type 2 who 27 people. Sampling method using accidental sampling technique. Family support was measured using a questionnaire support the family, while 3J diet obedience was measured using 24-hour recall for eating schedule and amount, while food frequency questionnaire for type of food. Result : Based on the chi-square analysis with p-value 1.000 (> 0,05), then Ho is accepted. Conclusion : So there is no relationship between family support with diet obedience in patients with diabetes mellitus type 2 Puskesmas Gamping 1 working area. Keywords: Diabetes mellitus, Family Support, Diet 3J